The technological impact of diffusion in nanopores - Ruthven, Douglas M. (Diffusion Fundamentals, 2005)
The impact of nanopore diffusion on the performance of adsorption separation processes is reviewed. Zeolite membrane processes and kinetically selective cyclic adsorption processes depend for their selectivity on differences in intracrystalline diffusion rates so these processes are designed to operate under conditions of intracrystalline diffusion control. In contrast, the performance of equilibrium based adsorption separation processes is adversely affected by diffusional resistance so in such processes the minimization of all resistances to mass transfer is a major design objective. Zeolite catalyzed reactions constitute a further important class of processes in which intrusion of diffusional resistance can be either advantageous or disadvantageous. Such effects are illustrated by considering in detail the conversion of methanol to light olefins (MTO) over SAPO34. Within the chemical process industries diffusion is important over a wide range of length scales. In this paper we focus only on diffusion at the nanometer scale since diffusional phenomena on this scale are critically important in adsorption separation processes as well as in many heterogeneous catalytic systems. Indeed membrane separations and molecular sieving adsorption processes (kinetic separations) are driven by differences in nanoscale diffusivities. For such processes the conditions of operation must therefore be selected so as to maximize the influence of nanoscale diffusion. This is true also for certain catalytic processes in which product selectivity can sometimes be improved by operating under conditions of diffusion control. More commonly, in equilibrium controlled adsorptive separations and in catalytic systems where activity rather than selectivity is the important feature, process performance is adversely affected by nanoscale diffusion, and in such systems it is obviously desirable to design the process in such a way as to minimize the intrusion of diffusional resistances. Some examples of both classes of process are discussed below.